A literatura no livro didático de língua portuguesa: a escolarização da leitura literária - Paula Cristina de Almeida (2006)
The use of literature in the didactic book of the Portuguese language in the first years of elementary school was the object of this research, that aimed at identifying the literary texts found in didactic collections and to analyze the choice for certain genres and authors, the incidence and positioning of texts. We investigated the adaptations required by the transferal of the literary text from its original support to the pages of the didactic book and the selection of the fragment that constitutes the text to be read; we also analyzed the proposed readings and comprehension activities that are presented in the didactic book for the work with the literary text. The corpus of this research is composed of 2 didactic collections of the Portuguese language, to be used in the first segment of elementary school, that were recommended by PNLD/2004 Programa Nacional do Livro Didático. The following collections were chosen by the public schools of Betim (located in Greater Belo Horizonte): Linhas e Entrelinhas, published by Nova Didática; and Bem-te-li, by FTD. The research was based on two main analysis procedures: quantitative approach and qualitative approach, which led to two moments of data collection. We could perceive, in the four volumes of each collection, the significant presence of literary texts that are representative and by renowned writers in our society. We could observe that the presence of activities for the comprehension abilities is quite significant, and that activities that explore the esthetic and literary processes of the text are proposed, but on both collections the literary text is also used as a pretext for the study of grammar topics, orthography, and for the acquisition of the alphabetical writing system. Both volumes 1 of the collections studied present more literary texts than the subsequent volumes, a trend that oriented us to choosing such books, used in the first year of elementary school, to analyze the process of transferal of the literary text to the pages of the didactic book and excerpts of reading and comprehension activities. The analysis revealed that fragments of the text, which misfigue the meaning of the authors work, are presented for reading and, moreover, inadequate procedures are used for teaching literary reading.